2019
DOI: 10.1111/lam.13243
|View full text |Cite
|
Sign up to set email alerts
|

Sources of food contamination in a closed hydroponic system

Abstract: This study investigated potential contamination sources in a commercial, closed hydroponic system. Water, substrate and lettuce (Lactuca sativa) samples were evaluated for microbiological indicator populations, including aerobic plate count (APC), coliform bacteria (CB) and yeast and mould (YM). Listeria spp. detection via cultural enrichment and agglutination was negative for all samples. Peat moss substrate (postharvest) had the highest counts for APC (6·8 log CFU per g), CB (4·5 log MPN per g) and YM (5·1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
2
16
1
Order By: Relevance
“…That is in line with the low Listeria spp. prevalence usually found in farms and hydroponic environments 4,27–29 . Although CB levels were higher than expected on plugs and roots (>4 log CFU g −1 ), the transfer of these bacteria to leaves by cross‐contamination appears to be minimal in our results.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…That is in line with the low Listeria spp. prevalence usually found in farms and hydroponic environments 4,27–29 . Although CB levels were higher than expected on plugs and roots (>4 log CFU g −1 ), the transfer of these bacteria to leaves by cross‐contamination appears to be minimal in our results.…”
Section: Discussioncontrasting
confidence: 53%
“…prevalence usually found in farms and hydroponic environments. 4,[27][28][29] Although CB levels were higher than expected on plugs and roots (>4 log CFU g −1 ), the transfer of these bacteria to leaves by cross-contamination appears to be minimal in our results. This finding disagrees with other work that showed a high coliform count on both hydroponically grown lettuce leaves (6.2 log CFU g −1 ) and plugs (5.9 log CFU g −1 ).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, Wang et al isolated Shiga toxin-producing E. coli from the leaf surface of hydroponic lettuce [ 12 ]. Dankwa also isolated 4.1 log CFU per g of aerobic bacteria by aerobic plate count from the leaves of harvested hydroponic lettuce [ 13 ]. These findings suggested that microbiological contamination of hydroponic produce is possible.…”
Section: Introductionmentioning
confidence: 99%